ZnO nanostructures for organometallic halide perovskite solar cells - Tam, Ho Won; Liu, Fangzhou; Wang, Yushu; Chen, Wei; Leung, Tik Lun; Djurišić, Aleksandra B; Ng, Alan Man Ching; Chan, Wai Kin; Tang, Jinyao (SPIE, 2018)
ZnO is considered a potential alternative of TiO2 for electron transport materials of perovskite solar cells due to its relatively high electron mobility and the ease of low temperature solution-processing. Nevertheless, ZnO-based perovskite devices usually exhibit inferior device performance and stability compared to TiO2 based devices due to the defect states at ZnO/perovskite interface. In this study, an ultrathin TiO2 layer by ALD is applied to ZnO nanostructures, and its effect on device performance is investigated. The results indicate that TiO2 ultrathin layer can effectively passivate the surface of ZnO nanostructures, resulting in enhanced device performance.